(untitled) (Journal of Libya for geographical studies, 2024)
This modest study aims to reveal the saucepan of changes occurring in vegetation patterns during the period between 1990 and 2020 and to monitor the trends of this change through spatial technologies such as (GIS), and remote sensing outputs through the analysis of satellite images provided by the Landsat satellite. The Vegetation Coverage Index (NDVI) provides valuable information about the health of plants and the changes occurring in them, based on the light interactions occurring in the two rays: near-infrared and red rays, bouncing off plants. The NDVI value is calculated for each cell in the image, and the resulting value indicates the condition and health of plants. It helps responsible authorities to make the most effective decisions in the fields of agriculture and natural resource management. This study was done to compare satellite visualizations taken in 1990, 2006, and 2019, apply the vegetation index equation, and analyze it spatially, based on several approaches consistent with the subject of this study. The results showed a discrepancy in the values ​​of the vegetation index between the periods specified for this study. If the index gave High values in any year, it may decrease in another year as a reflection of the state of rainfall occurring in the place. Thus, the areas and degree of vegetation coverage varied from year to year as a dependent variable, influenced by what may represent independent variables.